Homelessness Among Older Adults in Prague Causes, contexts and prospects - Vágnerová, Marie (Karolinum, 2020)
Following their engaging study Homelessness among Young People in Prague, the authors of this book turn their attention to an older population facing the same issue, a very different situation since these older adults grew up under a communist regime where an obligation to work was enshrined in law and living on the street could result in a prison sentence. Based on three years of research, this book provides a slew of data-based statistical insights, analyzing the efficacy of relief provided by both the state and nonprofit organizations, detailing how the clients of such organizations rate their services, to what extent they accept assistance, and whether they believe it has helped them. More importantly, it features extensive interviews with real people, making it the first Czech book on this issue to present homelessness from the perspective of those who live with it every day.
Keywords: Sociologie